'Hard to reach' parents but not hard to research: a critical reflection of gatekeeper positionality using a community-based methodology. Issue 5 (19th October 2020) - Wilson, Suzanne
ABSTRACT: Conducting research with under-represented, overlooked and service resistant groups poses challenges but can lead to valuable discoveries that inform the development of policy or practice. In this paper, a reflective account of a community-based methodology will be provided which targeted families in poverty who did not engage with the school system. The research discussed provides a phenomenological understanding of how these parents perceived their role in their child's education, and what challenges they felt they faced, both at home and in school. This community-based methodology proved effective in recruiting and obtaining data from five focus groups ( n = 27) and a series of in-depth interviews ( n = 50). The perceived positionality of the gatekeeper is discussed, explained using Tajfel and Turner's social identity theory [(1979). An Integrative Theory of Intergroup Conflict.' In The Social Psychology of Intergroup Relations, edited by W. G. Austin, and S. Worchel, 33–37. Monterey, CA: Brooks/Cole], with particular focus on in-group/out-group identity perceptions. The efficacy of the strategies used are discussed and recommendations for a community-based methodology for educational research is provided.